Mathematics for business analysis - Turner, Paul 1959- (Mercury Learning and Information, 2024)
Designed for students, faculty, and professionals, this book describes the role of mathematics in the world of economics and business. Beginning with the fundamental nature of numbers and progressing into more complex realms like hyperreal numbers and the intricacies of set theory, this book constructs a strong foundational understanding of mathematical concepts. The book uses PYTHON code throughout the text to illustrate problems numerically. As readers advance, the text seamlessly integrates essential topics such as linear simultaneous equations, which are pivotal in analyzing market equilibrium, and covers the mechanics of matrices for solving larger equation systems. Furthermore, chapters dedicated to calculus, especially its applications in economics and the innovative use of infinitesimal methods, equip learners with tools to tackle profit maximization challenges, factor optimization, and beyond. Later chapters unfold the world of differential and difference equations, revealing their significance in analyzing dynamic systems. All these concepts are illuminated through practical examples and numerous images from economics and business, ensuring relevance and clarity